Prison Sentence In The Middle Maghreb During The Ziyani Era And Its Aftermath On The Life Of The Prisoner - bougaada, bachir (Journal of Social Sciences and Humanities, 2022)
The author of this study seeks to search in a problem that revolves around the manifestations of suffering that prison sentence causes and its impact on the life of the prisoner in the middle Maghreb during the Ziyani era in all its aspects, whether it comes to imprisonment penalties resulting from the manifestations of war that the country witnessed when it was exposed to external aggression from the neighboring countries' leaders for various war aims and objectives, or in the midst of the conflict that has raged between the central authority and the tribal elements revolting against its authority within the territories of its state. Or be it, on the other hand, related to the prison sentence issued by the central political leadership against the opponents of the authority from among its citizens, that is to say, members of the political, administrative, and military apparatus. Or, even, to the prison sentence imposed against the scientific elites who expressed an opposing opinion to the vision of the ruling leadership, or adopted a hostile attitude against its policy, and the nature of its impact on their lives and their relationship with the authorities. Its importance lies in the fact that it aims at studying and analysing a delicate subject that did not receive adequate research attention. Despite the many studies that have dated the history of war and its aftermath on the population of the middle Maghreb during the medieval era and its extreme importance in the field of historical research. Cette étude examine la problématique de la peine d’emprisonnement dans le système pénitentiaire par le pouvoir zianide au Maghreb central, qu’il s’agisse soit des peines d'emprisonnement résultant des manifestations de la guerre, que le pays a connues lorsqu’il était attaqué de toutes les sortes des agressions extérieures, par les dirigeants des pays voisins aux divers buts et objectifs de la guerre, ou bien au milieu du conflit militaire qui se déroule entre les pouvoirs centraux et les éléments tribaux se révoltant contre leurs pouvoirs sur les territoires de leur pays. Soit en ce qui concerne la peine d’emprisonnement en tant qu'autorité disciplinaire pour les dirigeants de l'opposition politique et les maîtres du coup d'État militaire et leurs collaborateurs. En plus l’autorités zianide a adopté la prison, comme un mécanisme de punition et de discipline contre les élites scientifiques et religieuses, qui ne montrait pas une position conforme aux orientations de l'État ou exprimait des visions contraires à sa politique. Quant à la deuxième partie de cette étude, elle porte sur les conséquences les plus importantes que la peine de prison cause par rapport à la vie du prisonnier ou de la victime.